1989
DOI: 10.1128/aac.33.2.152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of free and liposomal amphotericin B and gramicidin S alone and in combination on potassium leakage from human erythrocytes and Candida albicans

Abstract: We studied the toxic effects of amphotericin B and gramicidin S, alone and in combination, using free and liposome-encapsulated drugs. In vitro toxic effects of the drugs on human erythrocytes and Candida albicans were determined by measuring leakage of intracellular potassium ions (K+). Liposomal formulations of both drugs greatly reduced K+ leakage from human erythrocytes, whereas liposomal gramicidin S, but not liposomal amphotericin B, prevented K+ leakage from C. albicans. In both free and liposomal forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…GS primarily acts as a defence molecule, but also retards the sporulation of its producer (Azuma & Demain, 1996;Nandi & Seddon, 1978). Both the anionic Srf and cationic GS have membranolytic activity (Maget-Dana & Ptak, 1995;Epand & Vogel, 1999) and are active against Gram-positive bacteria (Tsukagoshi et al, 1970; Kondejewski et al, 1996), as well as fungi (Midez et al, 1989;Tsukagoshi et al, 1970). However, Srf is generally less active than GS (this study), but possesses comparable haemolytic activity (Kracht et al, 1999;Katsu et al, 1988).…”
mentioning
confidence: 51%
“…GS primarily acts as a defence molecule, but also retards the sporulation of its producer (Azuma & Demain, 1996;Nandi & Seddon, 1978). Both the anionic Srf and cationic GS have membranolytic activity (Maget-Dana & Ptak, 1995;Epand & Vogel, 1999) and are active against Gram-positive bacteria (Tsukagoshi et al, 1970; Kondejewski et al, 1996), as well as fungi (Midez et al, 1989;Tsukagoshi et al, 1970). However, Srf is generally less active than GS (this study), but possesses comparable haemolytic activity (Kracht et al, 1999;Katsu et al, 1988).…”
mentioning
confidence: 51%
“…following 60 min exposure to lethal concentrations of the drug (6). We found that 3 h r exposure to 2.5 pg AmpBiml was necessary in order to maximize ETBR fluorescence of the cells (Fig 2).…”
Section: Discussionmentioning
confidence: 87%
“…1). Gramicidin S exhibits many clinically interesting features, including strong antibacterial and antifungal activity [1,2], broad immuno-suppressive properties [3], antitumor activity [4], DNA transfective properties [5] and protease inhibitor activities [6]. Since its discovery in the 1940s, more than 200 analogs of gramicidin S have been prepared and characterized chemically, physically *To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%